PENGARUH PENGETAHUAN KONSUMEN, PERASAAN KONSUMEN, MOTIVASI KONSUMEN, DAN KEPRIBADIAN KONSUMEN TERHADAP KEPUTUSAN PEMILIHAN PERGURUAN TINGGI (Studi Kasus Pada Program Regular I Universitas Mercu Buana) - Surahmat, Dede; Astini, Rina (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
This study aimed to examine and analyze the effect of consumer knowledge, consumer feeling, consumer motivation, and consumer personality on decision making for a higher education institution (Case study at the Regular Program of Universitas Mercu Buana). Research data for respondents were 385 regular program students complited, in September – December 2017, using purposive sampling method.  The analysis   used    was  Structural   Equation Model (SEM) and correlation between dimensions.  It showed   that   consumer   knowledge  had  not significant effect to the decision of University election. Consumers Feeling, consumer motivation, consumers   personality have significant effect to decision making of a University Selection